1989
DOI: 10.1097/00000658-198906000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal Shock-Wave Lithotripsy of Bile Duct Calculi

Abstract: A multi-institutional study to evaluate the efficacy, clinical application, and safety of extracorporeal shock-wave lithotripsy (ESWL) with the Dornier HM-3 or HM-4 lithotripter for bile duct calculi (BDC) was initiated in September, 1987. Symptomatic patients who entered into this prospective trial had BDC in the common bile duct and/or the intrahepatic, cystic or lobar ducts of the liver that were inaccessible or untreatable by papillotomy or percutaneous stone extraction. The study excluded gallbladder ston… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…ESWL uses shock waves generated from electrohydraulic or electromagnetic energy. The shock waves are transmitted from outside the body through soft tissue to the target (bile duct stones) under fluoroscopy guidance [ 41 ]. The first ESWL for the treatment of bile duct stones was reported in 1986 [ 42 ].…”
Section: Extracorporeal Shock-wave Lithotripsymentioning
confidence: 99%
“…ESWL uses shock waves generated from electrohydraulic or electromagnetic energy. The shock waves are transmitted from outside the body through soft tissue to the target (bile duct stones) under fluoroscopy guidance [ 41 ]. The first ESWL for the treatment of bile duct stones was reported in 1986 [ 42 ].…”
Section: Extracorporeal Shock-wave Lithotripsymentioning
confidence: 99%
“…This method of treatment clears retained bile duct stones in 60-90% of patients, although some patients require repeated treatments. [16][17][18][19][20][21] Mortality associated with ESWL ranges from 0-2%. Major adverse effects are uncommon even in the elderly.…”
Section: Mechanical Lithotripsymentioning
confidence: 99%
“…Major adverse effects are uncommon even in the elderly. [16][17][18][19][20][21] Cost is the major drawback with ESWL, particularly as there are several cheap and equally effective non-surgical alternatives. Furthermore, capital investment in ESWL is becoming even less attractive because laparoscopic cholecystectomy is rapidly reducing the indications for ESWL in biliary disease in general.…”
Section: Mechanical Lithotripsymentioning
confidence: 99%
“…By this means and including ESWL as well as local shocke-wave lithotripsy [52][53][54] the endoscopist is able to treat 90-95% of common bile duct stones with out the need of surgery [55][56][57][58]. Furthermore, it has been shown that selective preoperative endoscopic retrograde cholangiopancreatography and stone removal have very low morbidity and mortality in the laparoscopic treat ment of complicated gallstone disease [59].…”
Section: Common Bile Duct Stone Managementmentioning
confidence: 99%